The Pinochet Judgement: New Accountability for Old Dictators - Murphy, Sarah L (Victoria University of Wellington Law Review, 2001)
This article analyses the groundbreaking 1999 judgment of the House of Lords on the question of the extradition of Pinochet from the United Kingdom to Spain for crimes committed during his time as Head of State of Chile. It examines the two main components of the judgment: that Pinochet’s status as former Head of State of Chile did not allow him to benefit from sovereign immunity for acts of torture committed during his reignÍ¾ and that he could be extradited to Spain for acts of torture committed after 1989, when the United Kingdom codified its obligations under the Torture Convention. It supports the conclusion that the laws against torture override the immunity of former Heads of State, and suggests that the reasoning could be extended to apply to other crimes against humanity, and where the accused is an incumbent Head of State. On the question of extradition, it argues that the Law Lords had several avenues open under which Pinochet could have been extradited to face all counts of torture. It concludes with an analysis of the New Zealand legislation and case law on sovereign immunity, the prosecution of crimes against humanity, and extradition, and suggests several law reforms to bring New Zealand legislation in line with evolving international obligations to prosecute or extradite the perpetrators of crimes against humanity.